In-N-Out Burger : the perils of political contribution - Muldoon, Maria; Youdale, Rachel; O'Rourke, James S., 1946- (London : The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame, 2019)
On August 29, 2018 Eric Bauman, Chairman of the Democratic Party of California sent out a midnight tweet exposing In-N-Out Burger's donation of $25,000 to the Republican party and called for a nation-wide boycott. In-N-Out's response to the viral sensation could affect their reputation in their home state of California and alter their corporate political donation policy.
Originally Published InMuldoon, M., Youdale, R., & O'Rourke IV, J. S. (2019). In-N-Out Burger: The Perils of Political Contribution. 19-06. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; In-N-Out Burger (Firm) -- Political activity -- Case studies; Business and politics -- California -- Case studies